Two commercial suits compared: the case of Titianus Primus (Paul. 1 decr. d. 14, 5, 8) and Cicero's Pro Quinctio - Petrucci, Aldo (Ciceroniana On Line, 2022)
Ancient sources provide us with a wealth of information on two trials involving commercial disputes that took place more than three centuries apart. The first is reported by the jurist Julius Paulus at the beginning of the 3rd century AD and concerns a problem of contractual liability due to the non-payment by an agent of the price of a consignment of barley. We have extensive information about the context and proceedings: we know its stages (first instance and appeal judgement), the arguments put forward by the parties in support of their case and the sentences that conclude it. However, we have little in the way of the judicial rhetoric employed, as the material largely focuses on the treatment of the legal issues discussed and resolved. The second trial is the one in which a young Cicero delivered the Pro Quinctio in 81 B.C., a defence speech in proceedings concerning debts between partners. Unlike the first case, here we can fully appreciate the rhetorical skills displayed by the orator before the judge, but we do not know the outcome of the trial. The comparison of the two cases, despite the differences just highlighted, allows us to put forward some reflections on the role of judicial oratory even in proceedings on matters of a commercial nature, which apparently do not seem to need it.